Cover Image, Volume 53, Issue 2. (27th February 2020) - Zhang, Lei; Wang, Yi; Wu, Guorao; Rao, Lizong; Wei, Yanqiu; Yue, Huihui; Yuan, Ting; Yang, Ping; Xiong, Fei; Zhang, Shu; Zhou, Qing; Chen, Zhishui; et al.
Abstract : The cover image is based on the Original Article Blockade of JAK2 protects mice against hypoxia‐induced pulmonary arterial hypertension by repressing pulmonary arterial smooth muscle cell proliferation by Lei Zhang et al., https://doi.org/10.1111/cpr.12742 .